PENGARUH KUALITAS PELAYANAN, HARGA DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PT POS INDONESIA (PERSERO) - Septiana Chyntia dewi, 15.05.51.0035; Setiawan, Mulyo Budi (Students' Journal of Economic and Management, 2019)
This study aims to find out: (1) The magnitude of the influence of Service Quality on Customer Satisfaction of PT Pos Indonesia (Persero); (2) The magnitude of the effect of Price on Customer Satisfaction PT. Pos Indonesia (Persero); (3) The magnitude of the influence of Promotion on Customer Satisfaction PT. Pos Indonesia (Persero). The population in this study are all customers who use shipping services at PT Pos Indonesia (Persero). The number of samples used in this study were 100 respondents. The sampling technique in this study was using purposive sampling techniques. Data collection techniques are done by distributing questionnaires. Data analysis techniques used include description of research data, validity test, reliability test, prerequisite test analysis and hypothesis testing. Multiple linear regression test results show that service quality has a positive and significant effect on customer satisfaction, price does not have a significant effect on customer satisfaction, and promotion does not significantly influence customer satisfaction.